2016
DOI: 10.1111/jvim.14361
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value (Bayesian Framework) of Thoracic Ultrasonography over Thoracic Auscultation for Diagnosis of Bronchopneumonia in Preweaned Dairy Calves

Abstract: BackgroundThoracic ultrasonography (TUS) is a specific and relatively sensitive method to diagnose bronchopneumonia (BP) in dairy calves. Unfortunately, as it requires specific training and equipment, veterinarians typically base their diagnosis on thoracic auscultation (AUSC), which is rapid and easy to perform.Hypothesis/ObjectivesWe hypothesized that the use of TUS, in addition to AUSC, can significantly increase accuracy of BP diagnosis. Therefore, the objectives were to (i) determine the incremental value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 22 publications
(58 reference statements)
3
33
1
4
Order By: Relevance
“…This included a visual assessment of the steer for clinical signs associated with BP, specifically depression, cough, nasal discharge, and ocular discharge. A complete thoracic auscultation was also performed to detect abnormal lung sounds, as described [56]. Furthermore, a thoracic ultrasonography of the cranio-ventral portion of both sides of the thorax was performed to detect lung consolidation (> 1 cm deep) or pleural effusion, as described [57].…”
Section: Methodsmentioning
confidence: 99%
“…This included a visual assessment of the steer for clinical signs associated with BP, specifically depression, cough, nasal discharge, and ocular discharge. A complete thoracic auscultation was also performed to detect abnormal lung sounds, as described [56]. Furthermore, a thoracic ultrasonography of the cranio-ventral portion of both sides of the thorax was performed to detect lung consolidation (> 1 cm deep) or pleural effusion, as described [57].…”
Section: Methodsmentioning
confidence: 99%
“…This included a visual assessment of the steer for clinical signs associated with BP, specifically depression, cough, nasal discharge, and ocular discharge. A complete thoracic auscultation was also performed to detect abnormal lung sounds, as described [56]. Furthermore, a thoracic ultrasonography of the cranioventral portion of both sides of the thorax was performed to detect lung consolidation (> 1 cm deep) or pleural effusion, as described [57].…”
Section: Methodsmentioning
confidence: 99%
“…Previous work showed that punctual scoring of clinical signs is not accurate enough to confirm pneumonia 5 . Also inter‐rater variability is very large when using scorecards 6 A lot is expected from blood tests and automated detection systems, but to date lung auscultation and thoracic ultrasonography are the most accessible confirmation tests in the field. In the first instance most practitioners will rely on lung auscultation, but its diagnostic accuracy and inter‐rater variability are hardly documented.…”
Section: Figurementioning
confidence: 99%